A case study on the changes in the clothing styles of selected UP female students who have experienced street harassment - Alivio, Dinah Mae P.
A previous study shows that clothing is a factor that motivates men to commit harassment. With clothing as a factor to street harassment, the study identified the changes in the victims clothing styles, and analyzed these changes in terms of color, fit, and silhouette. A survey among 60 female students chosen through multi-phase sampling found that 95% experienced street harassment and 37% changed clothing styles. Furthermore, using an online questionnaire, it was determined that the selected respondents wore clothes that do not seek attention and emphasize their figure. It was also determined that they changed clothing silhouette to cover up more skin. Changes were mostly moderate and a few highly changed the way they dressed up for school. The study concluded that street harassment has a behavioural impact on the victims, as change in their clothing styles meant security for themselves. This study can pave way for brands to consider the feeling of security among its consumers and as a result, produce clothing with that purpose in mind.